Power conservation for electrically assisted rickshaw-vans with pv support, torque sensor pedal and the solar battery charging station : a complete off-grid solution (conducting field tests and data analysis for performance and feasibility study) - Khan, Fabiha Roshni; Rahman, Ataur; Aurony, Anika Tasnim (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2015.